EFFECT OF İN-OFFİCE BLEACHİNG ON THE SURFACE ROUGHNESS OF DİFFERENT COMPOSİTE RESİNS - Ozden Ozel Bektas; Seher Kaya (Cumhuriyet University, 2022)
Objective: The aim of this study is to investigate the effect of a high concentration hydrogen peroxide bleaching agent on the surface roughness of four different composite resins. Material and Methods: For this purpose, with the help of teflon molds, a total of 24 composite samples (10 x 2 mm) were prepared, with n = 6 for each composite group. The samples were placed in teflon molds in two layers of 2mm and covered by transparent mylar strips at the top and bottom surfaces. The material was compressed with finger pressure between 1mm thick glass plates. The tip of the light device was applied directly from the transparent tape surface for the polymerization of the samples. Polymerization of the samples was carried out using LED light device in each layer. After the samples were polished with finishing discs, they were kept at 37 ° C for 24 hours in the distilled water. Surface roughness values (Ra) of all samples were measured with a profilometer device. After the first measurements, a whitening agent containing 35% hydrogen peroxide was applied to the surfaces, and surface roughness measurements were repeated after this process. Data were analyzed statistically using analysis of variance (ANOVA) and Tukey tests. Results: Profilometric evaluations showed a small increase in the surface roughness of all samples with a bleaching agent. When the initial and treated measurements of the groups were compared, the difference between the measurements was found statistically insignificant. (P> 0.05) Conclusion: The office bleaching agent containing 35% hydrogen peroxide did not make any difference in the roughness of the nanohybrid and microhybrid composite resins.